2021
DOI: 10.3389/fmicb.2021.673444
|View full text |Cite
|
Sign up to set email alerts
|

Host Susceptibility Modulates Escovopsis Pathogenic Potential in the Fungiculture of Higher Attine Ants

Abstract: Health and disease emerge from intricate interactions between genotypes, phenotypes, and environmental features. The outcomes of such interactions are context-dependent, existing as a dynamic continuum ranging from benefits to damage. In host-microbial interactions, both the host and environmental conditions modulate the pathogenic potential of a microorganism. Microbial interactions are the core of the agricultural systems of ants in the subtribe Attina, which cultivate basidiomycete fungi for food. The fungi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 115 publications
0
6
0
Order By: Relevance
“…Interactions among Escovopsis strains cohabiting the same host may result in competition, inhibiting each other in the system (Christopher et al, 2021b ). Nevertheless, some associations are dynamic and can shift on the parasitism–mutualism continuum in response to environmental changes and/or the host susceptibility (Brown et al, 2012 ; Jiménez‐Gómez et al, 2021 ; Leung & Poulin, 2008 ; Mendonça et al, 2021 ). The capacity of Escovopsis to cause disease at the system‐level, and therefore trigger higher sanitization, may depend on the health and susceptibility condition of the superorganism, that is, the ants, the fungal cultivar, and the symbiotic community (Jiménez‐Gómez et al, 2021 ; Mendonça et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interactions among Escovopsis strains cohabiting the same host may result in competition, inhibiting each other in the system (Christopher et al, 2021b ). Nevertheless, some associations are dynamic and can shift on the parasitism–mutualism continuum in response to environmental changes and/or the host susceptibility (Brown et al, 2012 ; Jiménez‐Gómez et al, 2021 ; Leung & Poulin, 2008 ; Mendonça et al, 2021 ). The capacity of Escovopsis to cause disease at the system‐level, and therefore trigger higher sanitization, may depend on the health and susceptibility condition of the superorganism, that is, the ants, the fungal cultivar, and the symbiotic community (Jiménez‐Gómez et al, 2021 ; Mendonça et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, some associations are dynamic and can shift on the parasitism–mutualism continuum in response to environmental changes and/or the host susceptibility (Brown et al, 2012 ; Jiménez‐Gómez et al, 2021 ; Leung & Poulin, 2008 ; Mendonça et al, 2021 ). The capacity of Escovopsis to cause disease at the system‐level, and therefore trigger higher sanitization, may depend on the health and susceptibility condition of the superorganism, that is, the ants, the fungal cultivar, and the symbiotic community (Jiménez‐Gómez et al, 2021 ; Mendonça et al, 2021 ). Even so, we cannot exclude the chance that ants applied other prophylactic behaviors that were not measured in our study, such as metapleural gland grooming and the further discharge of infrabuccal pellets (Fernández‐Marín et al, 2013 , 2015 ; Yek et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, several studies provided evidence that some Escovopsis species act as specialized mycoparasite (Currie et al 1999a , 2003 ; Currie 2001 ; Gerardo et al 2004 ; Little and Currie 2007 ; de Man et al 2016 ). However, a recent study showed that Escovopsis species may act as an opportunistic fungus in attine ant colonies depending on host susceptibility (Jiménez-Gómez et al 2021 ). Either way, the parasitic mechanisms of the Escovopsis species that have a parasitic behaviour are still poorly understood, and the hypothesis of specialized mycoparasite for the genus was also raised considering Sympodiorosea spp., L. trichodermoides and the clades C and D (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Fungi from the genus Escovopsis have specialized in infecting attine ant fungal cultivars and represent the most significant threats to the ants’ food resources ( Figure 1 ; Meirelles et al, 2014 ; Jiménez-Gómez et al, 2021 ; Montoya et al, 2021 ). The fungal garden parasites have attained a level of specialization that is suggestive of co-evolution alongside the ants and their fungal cultivars ( Mueller et al, 2018 ; Douglas, 2022 ).…”
Section: The Order Hymenopteramentioning
confidence: 99%
“…At the same time, compounds derived from hymenopteran-actinomycete defensive mutualisms can display remarkable pathogen specificity. Dentigerumycin, for example, selectively inhibits Escovopsis pathogens of attine ants while causing no harm to the mutualistic fungus of the ants ( Oh et al, 2009 ; Jiménez-Gómez et al, 2021 ). Finally, actinomycete associations with hymenopterans may select for compounds with low toxicity toward animal cells ( Chevrette et al, 2019 ).…”
Section: Bioactive Potential Of Hymenopteran-associated Actinomycetesmentioning
confidence: 99%